Update on bazedoxifene: A novel selective estrogen receptor modulator - Diane M Biskobing (Dove Medical Press, 2007)
Diane M BiskobingDepartment of Medicine, Virginia Commonwealth University, Richmond, VA, USAAbstract: In the elderly population, osteoporosis is a significant clinical problem leading to disability and even death. Many patients remain untreated, despite effective therapies, because of patients’ unwillingness to take current therapies or inability to tolerate the therapies. For this reason, ongoing research continues to search for more effective and tolerable osteoporosis agents. Bazedoxifene is a selective estrogen receptor modulator (SERM) currently in development for osteoporosis prevention and treatment. A new drug application (NDA) for postmenopausal osteoporosis prevention was recently submitted to the FDA. Preclinical and clinical studies with bazedoxifene demonstrate more tissue selectivity than other SERMs. In particular, bazedoxifene has minimal if any agonist activity in the uterus and is able to antagonize effects of estrogen on the uterus. Animal studies and early clinical studies suggest effects in the bone similar to other SERMs with prevention of postmenopausal bone loss. Until more data on efficacy and safety are published, however, its role in osteoporosis is unknown. Keywords: osteoporosis, bazedoxifene, selective estrogen receptor modulator, postmenopause, prevention